1979
DOI: 10.1542/peds.63.4.679
|View full text |Cite
|
Sign up to set email alerts
|

Antacid Bezoar in a Newborn

Abstract: Antacid therapy is commonly used in the medical management of peptic ulcers and massive gastric bleeding. A similar approach has been employed in newborn infants with stress ulcers in order to reduce the total load and concentration of gastric hydrochloric acid during massive acute gastric bleeding.1 Antacid therapy may cause aluminum hydroxide "bezoar" in a newborn infant. This report confirms this possibility and suggests a rationale for its occurrence and therapy. CASE REPORT T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Both Mg alginate and thickened formula were not associated with significant clinical adverse effects. Adult studies demonstrated that sodium alginate can cause electrolyte disorders (29), whereas in pediatric populations it has been demonstrated that precipitation of alginate in the stomach can form a bezoar, responsible for a possible increase in reflux frequency (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Both Mg alginate and thickened formula were not associated with significant clinical adverse effects. Adult studies demonstrated that sodium alginate can cause electrolyte disorders (29), whereas in pediatric populations it has been demonstrated that precipitation of alginate in the stomach can form a bezoar, responsible for a possible increase in reflux frequency (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%